'[Her] hostess … is anxious to have her back when she is cured': The impact of the evacuation of children on wartime local services, England, 1939–1945. Issue 2 (29th May 2020) - Taylor, Jonathan
Abstract : World War II had a profound, but uneven, impact on the delivery of services designed to support the bodies and minds of English children. This article, which is based on a study of a rural local authority located in North-West England, explores the influence of World War II on children's welfare services. Drawing on detailed case files relating to individual children and reports published by local and national policy makers, the article advances three related arguments which together nuance existing understandings of the conflict and its longer-term consequences. First, the article argues that many of the problems associated with evacuees were already familiar to medical and social work professionals. This awareness has important consequences for how we conceptualise the wartime proposals that attracted policy makers' attention. Second, the article shows that the arrival of evacuees into reception areas initially resulted in an expansion of children's services. A fuller understanding of Britain's welfare state, however, must acknowledge that local authorities continued to wield significant influence over the delivery of specialist services once the conflict ended. As a result, the priorities of local officials could lead to the needs of looked after children being overlooked despite wartime improvements to children's services. Finally, the article argues that amidst the totality of World War II, the British state remained unwilling to intrude on the rights of parents to influence the care of their children. Closer examination of the implementation of evacuation and the experiences of individuals reveals that important tensions existed between the state appointed experts and the civilians they were tasked with supporting.